2018
DOI: 10.1111/ijcp.13289
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of emergency medicine clinical practice guidelines: Do we agree?

Abstract: Background: Clinical practice guidelines (CPGs) have been published by the American College of Emergency Physicians (ACEP) since 1990 to advance evidence-based emergency care. ACEP clinical policies have drawn anecdotal criticism for bias, yet the overall quality of these guidelines has not previously been quantified. We sought to examine ACEP clinical policies using a recognized, validated appraisal instrument: Appraisal of Guideline for Research & Evaluation (AGREE II). Methods: Systematic assessment of curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…Previous studies regarding the quality of CPGs were limited to specific health topics or regions [2139] and systematic reviews using these studies [4042]. Regarding the relationship between quality and application of CPGs, O’Sullivan et al clarified that high “scores in some domains of AGREE II tool were significantly associated with reductions in nonadherent testing” [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies regarding the quality of CPGs were limited to specific health topics or regions [2139] and systematic reviews using these studies [4042]. Regarding the relationship between quality and application of CPGs, O’Sullivan et al clarified that high “scores in some domains of AGREE II tool were significantly associated with reductions in nonadherent testing” [32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AGREE II items and domains can affect the overall assessment. Although several studies have revealed the correlation between domain scores and the overall assessment, they did not adjust the influence between domains [30, 39, 40]. Adjusting such influence, Hoffman-Eßer et al demonstrated the influence of domains on the overall assessment [42].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the CPG implementation process in emergency care settings is de cient. This lack may be explained by CPG development and implementation processes being separate activities (48), or it may exist because CPG developers are not involved in everyday emergency clinical work. In summary, our result con rms that existing evidenced-based CPGs are not in use in Swedish emergency care and that the shortage of evidence-based CPGs may result in patients not being provided the best care and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If not GRADE, then what framework should GRACE use? EM stakeholders’ evaluation of 20 clinical policies using the Appraisal of Guideline for Research and Evaluation (AGREE II) instrument noted significant problems with applicability and issues with stakeholder involvement and clarity of presentation of current guidelines 33 . Furthermore, a similar analysis of the levels of evidence supporting ACEP policy recommendations found that the majority of these were supported by lower classes of evidence and primarily expert opinion based 34 .…”
Section: Figurementioning
confidence: 99%